2015
DOI: 10.1111/imj.12667
|View full text |Cite
|
Sign up to set email alerts
|

Increased interventricular septum wall thickness predicts all‐cause death in patients with coronary artery disease

Abstract: Thickened IVS can be served as a reliable marker for predicting all-cause death in Chinese patients with CAD, even in those with normal left ventricular mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…After further correction for age and gender, associations remain significant for insulin levels, HOMA-IR, and AHI. Previously, multiple studies established that increased IVST is associated with an adverse metabolic profile [40][41][42], higher blood pressure in young healthy adults [43,44], and higher all-cause mortality in adults with cardiovascular disease [45,46]. Our findings support the hypothesis that hyperinsulinemia plays a role in the nonhemodynamic pathogenesis of cardiac hypertrophy, albeit limited to the ventricular septum.…”
Section: Discussionsupporting
confidence: 86%
“…After further correction for age and gender, associations remain significant for insulin levels, HOMA-IR, and AHI. Previously, multiple studies established that increased IVST is associated with an adverse metabolic profile [40][41][42], higher blood pressure in young healthy adults [43,44], and higher all-cause mortality in adults with cardiovascular disease [45,46]. Our findings support the hypothesis that hyperinsulinemia plays a role in the nonhemodynamic pathogenesis of cardiac hypertrophy, albeit limited to the ventricular septum.…”
Section: Discussionsupporting
confidence: 86%
“…In a study of hypertensive patients receiving regular treatment, multivariate adjusted analysis showed that greater IVST at baseline was associated with worse cardiovascular outcomes during 5 years of follow-up [28]. Huang et al [29] concluded that thickened IVS can be served as a reliable marker for predicting all-cause death in Chinese patients with coronary artery disease, even in those with normal LVM. Graham-Brown et al [30] compared global and segmental native myocardial T1 time of 35 hemodialysis patients and 22 control individuals and found that the median native global T1 time was significantly higher in the hemodialysis group (1,270 vs. 1,085 ms), with the septal regions of hemodialysis patients having significantly higher median T1 times than nonseptal regions (1,293 vs. 1,252 ms).…”
Section: Discussionmentioning
confidence: 99%
“…While IVS hypertrophy in adults predicts all cause death in coronary artery disease [40] , the predictive role of IVS hypertrophy for all deaths in children recipients of LROLT still awaits further research.…”
Section: Discussionmentioning
confidence: 99%